Managing Services - Haynes, Kathryn; Grugulis, Irena (Ascent Audio, 2019)
The nature of services in society and the economy is wide-ranging and complex, and the management of services and their innovation provokes a number challenges for practitioners, professionals, and academics. This book provides a range of perspectives on understanding, managing, and reconceptualizing service by bringing together contributions from leading figures in service research, to make a timely and significant multi-disciplinary contribution to the theory and practice of service management. The book presents a collection of contemporary perspectives on service management challenges, extending the understanding of service through exploration and critique of service organizational and managerial strategies from selected theoretical and empirical perspectives. Amongst other contributions, it reviews the importance of service to academics, professionals, and practitioners; evaluates selected aspects of the practice of service management, and investigates the challenges inherent in managing services; reviews the nature, direction, and applicability of selected theoretical dimensions which inform the understanding of service management; and assesses the opportunities for theory building, to further support understanding of the complexities of service management and its impact on organisations and wider society.